2001
DOI: 10.1073/pnas.181484498
|View full text |Cite
|
Sign up to set email alerts
|

Biological clock in total darkness: TheClock/MOP3circadian system of the blind subterranean mole rat

Abstract: Blind subterranean mole rats retain a degenerated, subcutaneous, visually blind but functionally circadian eye involved in photoperiodic perception. Here we describe the cloning, sequence, and expression of the circadian Clock and MOP3 cDNAs of the Spalax ehrenbergi superspecies in Israel. Both genes are relatively conserved, although characterized by a significant number of amino acid substitutions. The glutamine-rich area of Clock, which is assumed to function in circadian rhythmicity, is expanded in Spalax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 49 publications
(76 reference statements)
5
38
0
Order By: Relevance
“…We have already shown that a CLOCK͞MOP3-driven clock exists in Spalax (8). Here we continue to decipher its circadian machinery.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…We have already shown that a CLOCK͞MOP3-driven clock exists in Spalax (8). Here we continue to decipher its circadian machinery.…”
mentioning
confidence: 80%
“…We cloned, sequenced, and unraveled the expression of the circadian Clock and MOP3 cDNAs of three species of the S. ehrenbergi superspecies in Israel (8). Both genes are relatively conserved, yet Clock displays a unique Q-rich area as compared with other mammals, assumed to function in circadian rhythmicity, and Spalax CLOCK͞MOP3 dimer is less potent than its human counterpart in driving transcription.…”
Section: The Evolutionary Model Of Blind Subterranean Mammalsmentioning
confidence: 99%
“…Of special interest is the high expression of heparanase in the Spalax eye (Fig. 4B, lane 6), which is atrophic and visually blind (16,17), but is assessing photoperiodicity by responding to signals that penetrate the soil and is also involved in the circadian rhythm control (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mole rats have degenerated, subcutaneous eyes that are visually nonfunctional, but are engaged in circadian entrainment and have increases in retinal projections to structures involved in photoperiodic and photo-neuroendocrine regulation (1-3). Moreover, the circadian rhythm transcription factor CLOCK of the blind mole rat has an expanded glutamine-rich domain that may cause a change in its transcriptional activity (33). In addition, the rhodopsin gene of Spalax is functional in retinal cells despite the overall degenerate eye (34), as is true for melanopsin and pituitary adenylate cyclase-activating peptide (PACAP) (J. Hannibal, P. Hindersson, E.N., and J. Fahrenkrug, unpublished results).…”
Section: Discussionmentioning
confidence: 99%